Acute Moist Dermatitis with Thrombocytopenia in Cat - Kurnia Desiandura; Intan Permatasari Hermawan; Hana Cipka Pramuda Wardhani; Era Hari Mudji Restijono; Palestin . (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Abstract Background: The causes of cases of Acute Moist Dermatitis (AMD) or also known as hotspots are numerous. Early AMD is accompanied by symptoms of pruritus or different behaviors triggered by itching such as scratching or licking. Many causes of pruritus in cats such as hypersensitivity dermatitis, ectoparasites, fungal infections, bacterial infections, or skin reactions to systemic diseases. Gradually clinical symptoms will occur alopecia and erythema because it is very itchy, moist and smells on the surface of the skin. Case Description: A male Persian cat, 1.6 years old and weighing 3.4 kg, presented with a history of pruritus, alopecia, erythema and wet skin in several locations, especially around the neck, and had been present for 3 months. Appetite to eat and drink is not very good because the cat is busy scratching and biting its fur due to excessive itching. Examination Results and Treatments: After clinical examination and microscopic examination of samples, the main trigger in this case was furmite in a cat, Lynxacarus radovskyi with secondary bacterial infection causing Acute Moist Dermatitis (AMD). Not only that, ectoparasites in this case also cause other systemic diseases, namely suspicion of blood parasites that cause thrombocytopenia as evidenced by the results of a Complete Blood Count (CBC), and is characterized by clinical symptoms of hematuria and epistaxis. This cat underwent intensive treatment for several weeks with several combinations of drugs such as antiparasitics, antibiotics. antihistamines, NSID and vitamins. Conclusion: This